1998
DOI: 10.1038/sj.leu.2401168
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-2 family of proteins in fresh myeloma cells

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…81 The importance of the Bcl-2 family of proteins is underscored by reports of their dysregulation in many hematological malignancies that can contribute to the resistance of such malignancies to pro-apoptotic chemotherapeutic drugs. [82][83][84][85][86][87][88][89][90] Apoptosis due to the cell receiving an abnormal proliferative signal…”
Section: The Bcl-2 Family Of Proteins: the Finger On The Buttonmentioning
confidence: 99%
“…81 The importance of the Bcl-2 family of proteins is underscored by reports of their dysregulation in many hematological malignancies that can contribute to the resistance of such malignancies to pro-apoptotic chemotherapeutic drugs. [82][83][84][85][86][87][88][89][90] Apoptosis due to the cell receiving an abnormal proliferative signal…”
Section: The Bcl-2 Family Of Proteins: the Finger On The Buttonmentioning
confidence: 99%
“…29 In large B-cell non-Hodgkin's lymphoma, multiple myeloma, or anaplastic large cell lymphoma (ALCL), overexpression of Bcl-2, or an increased number of Bcl-2-positive cells, correlated with poor prognosis. [36][37][38][39] Additionally, numerous studies have demonstrated Bcl-2 overexpression, and a correlation with poor prognosis, in nonhematological cancers, such as melanoma, [40][41][42] breast cancer, [43][44][45][46] prostate cancer, [47][48][49] small cell lung cancer (SCLC), 50,51 colorectal carcinoma, 52,53 bladder transitional cell carcinoma, [54][55][56][57] and solitary fibrous tumors. 58 Bcl-X L has also been implicated in the pathogenesis of several types of cancer.…”
Section: Deregulated Expression Of Bcl-2 and Bcl-x L In Human Malignamentioning
confidence: 99%
“…61 Advanced and relapsed cases of multiple myeloma are characterized by high levels of Bcl-X L ; 61 earlier stages of the disease manifest higher levels of Bcl-2. 38 In nonhematological cancers, elevated levels of Bcl-X L were detected in bladder transitional cell carcinoma, 62 and squamous cell cancer of the oropharynx, and correlated with poor remission after radiotherapy. 63 Both Bcl-X L and Bcl-2 are expressed in breast cancers.…”
Section: Deregulated Expression Of Bcl-2 and Bcl-x L In Human Malignamentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 is expressed in myeloma cell lines and in myeloma patients' samples despite the absence of molecular evidence of Bcl-2 rearrangements. [16][17][18][19][20][21][22] Bcl-2 inhibits apoptosis by forming inactivating heterodimers with proapoptotic Bcl-2 family proteins, and by preventing the collapse of the mitochondrial transmembrane potential, the release of cytochrome c and Smac/DIABLO from mitochondria into the cytosol, and the activation of caspases. [23][24][25][26] Overexpression of Bcl-2 in transgenic mice prolongs the lifespan of plasma cells and in combination with abnormal expression of other oncogenes such as c-Myc, contributes to the development of immature pre-B-cell lymphoma, large-cell lymphoma or plasmacytoma in 40-60% of the mice.…”
Section: Introductionmentioning
confidence: 99%